The Effects of Intergroup Competition and Intragroup Cooperation on Slack and Output in a Manufacturing Setting. - Young, S. Mark; Fisher, Joseph; Lindquist, Tim M. (The Accounting Review, 1993)
Firms are redesigning operations to reduce slack and waste and improve performance (Hoerr 1989; Safizadeh 1991; Walton 1987) and this often involves reorganizing production workers into workgroups to foster cooperation and group participation in setting standards (Hayes et al. 1988; Schonberger 1986). In addition to employing incentive schemes linked to meeting standards, many firms are using bonuses tied to relative performance among groups to develop a spirit of intergroup competition. Over the past two years, we made several visits to three Fortune 500 manufacturing firms involved in such changes. The site visits suggested several hypotheses that merited further investigation. Thus, we designed a laboratory experiment to study more systematically what we had observed in the field. This study extends previous research on determinants of slack and performance (e.g.. Chow 1983; Chow et al. 1988; Waller and Chow 1985; Young 1985) by: (1) incorporating our observations and the literature on intragroup cooperation and competitive feedback to develop hypotheses, (2) studying workgroups rather than individuals, and (3) using a multiperiod rather than single-period setting. Results of the experiment show that the type of competitive feedback received by groups affected both their output and slack. Interestingly, when individuals were allowed to cooperate rather than work In isolation, performance actually declined. This latter result was unexpected and was likely the consequence of the particular experimental task.